2019
DOI: 10.1002/gch2.201900027
|View full text |Cite
|
Sign up to set email alerts
|

Binder‐Free 3D Integrated Ni@Ni3Pt Air Electrode for Zn–Air Batteries

Abstract: Developing an air electrode with high efficiency and stable performance is essential to improve the energy conversion efficiency and lifetime of zinc–air battery. Herein, Ni3Pt alloy is deposited on 3D nickel foam by a pulsed laser deposition method, working as a stable binder‐free air electrode for rechargeable zinc–air batteries. The polycrystalline Ni3Pt alloy possesses high oxygen‐conversion catalytic activity, which is highly desirable for the charge and discharge process in zinc–air battery. Meanwhile, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Figure S9 (Supporting Information) presents low-resolution CS-STEM images, which confirmed that the numerous defect sites in TiC can be served as efficient catalytic sites. [45] Additionally, the Raman spectra (Figure S10, Supporting Information) of Black Ti show three peaks at ≈ 270, 440, and 605 cm −1 , which were almost consistent with previously published results related to TiC, [32] and the slight difference may be attributed to the nonstoichiometric nature of TiC. [46] To verify the uniformity of the TiC, SEM-EDS elemental mapping was performed.…”
Section: Synthesis Of Black Ti and Characterization Of Tic Formed On ...supporting
confidence: 87%
“…Figure S9 (Supporting Information) presents low-resolution CS-STEM images, which confirmed that the numerous defect sites in TiC can be served as efficient catalytic sites. [45] Additionally, the Raman spectra (Figure S10, Supporting Information) of Black Ti show three peaks at ≈ 270, 440, and 605 cm −1 , which were almost consistent with previously published results related to TiC, [32] and the slight difference may be attributed to the nonstoichiometric nature of TiC. [46] To verify the uniformity of the TiC, SEM-EDS elemental mapping was performed.…”
Section: Synthesis Of Black Ti and Characterization Of Tic Formed On ...supporting
confidence: 87%
“…process, causing vulnerable stability in the liquid Zn-air fuel cell system. [11][12][13] Actually, the pore structure has an important influence on the ORR reaction process of metal-air batteries. [14,15] For example, many previous researches have indicated that the pore structure and pore size will greatly affect the diffusion of gas and electrolyte, which is closely related to the reaction kinetics of ORR.…”
mentioning
confidence: 99%
“…From this point of view, the coin cell, which is also frequently used, represents an actual optimization, because here, the entire zinc reservoir is located in the cell and is in contact with the electrolyte. [116][117][118][119][120][121][122][123][124][125] However, the coin cell setup also causes problems in the operation of the zinc-air battery and is not to be advocated without further ado. The schematic cross-section of a zinc-air battery in coin cell configuration illustrates the problem originating from the extensive contact between zinc anode and the electrolyte in such a configuration (Figure 6).…”
Section: A View On Cell Designmentioning
confidence: 99%